Hope of progress - Medawar, P. B. (London, 1972)
This collection of essays and lectures is addressed to scientists and to all who are inter ested in the history of scientific ideas and the impact of science on society. The principle piece in this new collection is the author's 1969 presidential address to the British Association 'On The Effecting of All Things Possible', an argument for believing in the ability of science to solve the problems it has itself created, and which too many of us be lieve insoluble. "To deride the hope of pro gress is the ultimate fatuity, the last word in poverty of spirit and meanness of mind.' Also included is the author's Romanes Lec ture on 'Science and Literature' (with a Reply by John Holloway and a Rejoinder by the author), and a well known critique of J. D. Watson's notorious account of the discovery of the molecular structure of DNA, The Double Helix. Other chapters discuss the possibility of the control and domination by science of the body and mind of Man - though the author concludes in 'The Genetic Improvement of Man': 'I think that, in the main, for many centuries to come, we shall have to put up with human beings as they are at present constituted'.
Keywords: Science social aspects